Equivalent Surface Impedance of Slot Impedance Load Based on the Aperture in a Parallel-Plate Waveguide Wall as Part of an Infinite Array - O. V. Alpatova; V. G. Koshkid’Ko (Известия высших учебных заведений России: Радиоэлектроника, 2016)
The problem of infinite array of slot impedance loads excitation by plane wave is considered in order to determine the equivalent surface impedance. Each array element is an aperture in the wall of parallel-plate waveguide. A plane conductor is placed in the aperture. Fields representation as expansion in Floquet harmonics was used, the solution is reduced to integral equation calculated by the Krylov-Bogolyubov method. Numerical results are obtained as an equivalent surface impedance dependency on the aperture size, strip conductor size in the aperture and on the plane wave incidence angle. A comparative analysis of obtained dependencies with single impedance load characteristics is carried out.